2008
DOI: 10.1073/pnas.0808431105
|View full text |Cite
|
Sign up to set email alerts
|

Late onset muscle plasticity in the whisker pad of enucleated rats

Abstract: Blindness leads to a major reorganization of neural pathways associated with touch. Because incoming somatosensory information influences motor output, it is plausible that motor plasticity occurs in the blind. In this work, we evaluated this issue at the peripheral level in enucleated rats. Whisker muscles in enucleated rats 160 days of age or older showed increased cytochrome oxidase activity, capillary density, motor plate size, and amplitude of evoked field potentials as compared with their control counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Although previous work suggests that incremental increases in neuronal activity associated with enhanced somatosensory experience lead to S1 expansion in birth-enucleated rodents [9], [10], the present results weaken this notion. The observations that support our conclusions are: 1) The size and growth rate of whiskers in birth-enucleated rats are similar to those observed in control sighted rats; 2) The magnitude of barrel expansion was similar between young and adult rats enucleated at birth; 3) Unilateral dewhiskering at 168 h did not prevent barrel expansion in the deprived hemisphere nor did it produce barrel overgrowth in non-deprived hemispheres of birth-enucleated adult rats; 4) Neither enucleation after the period of barrel formation nor raising rats in complete darkness promoted barrel expansion; 5) Metabolic markers of neuronal activity (CyOx and 2DG) were comparable in the trigeminal ganglion and/or in non-expanded and expanded PMBSF barrels of control and birth-enucleated rats, respectively, at different ages; and 6) Barrel expansion in birth-enucleated rats took place before the onset of active whisking (PD12)[55][59], and before cortical-evoked activity [60][62].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous work suggests that incremental increases in neuronal activity associated with enhanced somatosensory experience lead to S1 expansion in birth-enucleated rodents [9], [10], the present results weaken this notion. The observations that support our conclusions are: 1) The size and growth rate of whiskers in birth-enucleated rats are similar to those observed in control sighted rats; 2) The magnitude of barrel expansion was similar between young and adult rats enucleated at birth; 3) Unilateral dewhiskering at 168 h did not prevent barrel expansion in the deprived hemisphere nor did it produce barrel overgrowth in non-deprived hemispheres of birth-enucleated adult rats; 4) Neither enucleation after the period of barrel formation nor raising rats in complete darkness promoted barrel expansion; 5) Metabolic markers of neuronal activity (CyOx and 2DG) were comparable in the trigeminal ganglion and/or in non-expanded and expanded PMBSF barrels of control and birth-enucleated rats, respectively, at different ages; and 6) Barrel expansion in birth-enucleated rats took place before the onset of active whisking (PD12)[55][59], and before cortical-evoked activity [60][62].…”
Section: Discussionmentioning
confidence: 99%
“…BE rats [82]. These results suggest that, in the absence of eyes from early life, the rodent skin develops a condition characterized by a deregulated immune response that can be evidenced by sensitizing and challenging birth-enucleated rodents with OXA and/or DFBN.…”
Section: Shifts In Detc Density Do Not Explain Exacerbated Dsch Respo...mentioning
confidence: 77%
“…Here, we found the epidermis thickened ( Figure 1 c–f and Figure 6 a,b; see also [ 81 ] for a similar result in rats) and some of the proinflammatory cytokines involved in regulating keratinocyte growth and differentiation (e.g., IL4, IL6 and IL17) upregulated two months after enucleation at birth. In a previous study, neurotrophin-3 was also found to be increased in the whisker muzzle of BE rats [ 82 ]. These results suggest that, in the absence of eyes from early life, the rodent skin develops a condition characterized by a deregulated immune response that can be evidenced by sensitizing and challenging birth-enucleated rodents with OXA and/or DFBN.…”
Section: Resultsmentioning
confidence: 96%